Efficacy Validation of the Revised First Step Program: A Randomized Controlled Trial. (January 2021) - Feil, Edward G.; Walker, Hill M.; Frey, Andy J.; Seeley, John; Small, Jason W.; Golly, Annemieke; Lee, Jon; Forness, Steve R.
Disruptive behavior problems frequently emerge in the preschool years and are associated with numerous, long-term negative outcomes, including comorbid disorders. First Step is a psychosocial early intervention with substantial empirical evidence supporting its efficacy among young children. The present study reports on a validation study of the revised and updated First Step early intervention, called First Step Next, conducted within four preschool settings. One hundred sixty students at risk for school failure, and their teachers, were randomized to intervention and control conditions. Results indicated coach and teacher adherence to implementing the core components of the program was excellent. Teachers and parents had high satisfaction ratings. For the three First Step Next prosocial domains, Hedges' g effect sizes (ESs) ranged from 0.34 to 0.91. For the problem behavior domain, children who received the First Step Next intervention had significant reductions in teacher- and parent-reported problem behavior as compared to children randomized to the control condition. For the problem behavior domain, Hedges' g ESs ranged from 0.33 to 0.63, again favoring the intervention condition. All of the domains were statistically significant. This study builds on the evidence base supporting the First Step intervention in preschool settings.